Family Flexiviridae: A case study in virion and genome plasticity - Martelli, G.P.; Adams, M.J.; Kreuze, Jan F.; Dolja, V.V. (Annual Reviews, 2007)
The plant virus family Flexiviridae includes the definitive genera Potexvirus, Mandarivirus, Allexivirus, Carlavirus, Foveavirus, Capillovirus, Vitivirus, Trichovirus, the putative genus Citrivirus, and some unassigned species. Its establishment was based on similarities in virion morphology, common features in genome type and organization, and strong phylogenetic relationships between replicational and structural proteins. In this review, we provide a brief account of the main biological and molecular properties of the members of the family, with special emphasis on the relationships within and among the genera. In phylogenetic analyses the potexvirus-like replicases were more closely related to tymoviruses than to carlaviruses. We postulate a common evolutionary ancestor for the family Tymoviridae and the two distinct evolutionary clusters of the Flexiviridae, i.e., a plant virus with a polyadenylated genome, filamentous virions, and a triple gene block of movement proteins. Subsequent recombination and gene loss would then have generated a very diverse group of plant and fungal viruses.